Analisis Marketing Mix terhadap Produk Tadyra (Tabungan Ady Hari Raya) di BPR ADY JEMBER Cabang Rambipuji - Rahma Dwi Mayasari; Risalatul Muawanah (CV. ITTC INDONESIA, 2024)
Marketing mix is asset of marketing variabels, wichh are used by companies to pursue desired sales targets. The purpose of writing this journal is to find out the marketing mix against the savings product on BPR ADY JEMBER Cabang Rambipuji through direct observation. The type of research used is qualitative research, which is type of study that has descriptive properties and tend to use analysis. The data-gathering technique used is through interviews and live observation. Based on thr results of the following research it can be concluded that the marketing mix on BPR ADY JEMBER Cabang Rambipuji has gone well and according to the regulations in force, although less maximum and still there are obstacles faced